Korelasi minat dan metode tutor sebaya terhadap hasil belajar siswa kelas IV SD Negeri Sampangan Yogyakarta - Nurmaningtyas, Isna; Andini, Dinar Westri; Taryatman, Taryatman (Universitas Sarjanawiyata Tamansiswa, 2024)
This study aims to 1) Determine the relationship between peer teaching methods and learning outcomes; 2) Determine the relationship between student interest and learning outcomes; 3) Determine the relationship between peer teaching methods and student interest in learning outcomes. This research is quantitative research with a correlational research type. The population in this study are students of class IV B SD N Sampangan Yogyakarta. Data collection techniques use questionnaire instruments. Data analysis techniques are processed with PLS-SEM analysis and regression analysis using SmartPLS. The results of the study show that: 1) There is a positive relationship between peer teaching methods and learning outcomes with a t-statistic value of 2.04 > 1.96 and a p-value of 0.041 < 0.05; 2)There is a positive relationship between student interest in learning outcomes with a t-statistic value of 2.33 > 1.96 and a p-value of 0.020 < 0.05; 3) There is a relationship between peer teaching methods and student interest simultaneously towards learning outcomes with an F count value = 40.597 and a p- value = 0.000. The R2 value = 0.750 means that 75% of students learning outcomes are influenced by peer teaching methods and student interest, while the remaining 25% are influenced by other variables outside the research variables, such as learning readiness and parenting patterns.